Penggunaan Media Online dalam Proses Belajar Mengajar di Masa Pandemi Covid-19 : Studi Kasus di SD Talaga 2 Cikupa - Zahranisa, Anida; Asmawati, Asmawati; Sutiani, Komang; Marlina, Nana; Aulia, Shinta (ANWARUL, 2022)
The covid-19 pandemic conditions cause unprecedented changes in life, and so learning is made online from home through online media (online), where teachers are required to use technology to design learning media as an innovation. This type of research employs a qualitative approach with a descriptive method. Data retrieval takes place through interview techniques, observation and documentation. The data-analysis technique is done in a descriptive way by describing the student's interview results. Studies have found that teachers still encounter obstacles to the online use of the learning media and that it takes teacher creativity to create the learning media by using various platforms